Biologic therapy for acrodermatitis continua of Hallopeau: Successful treatment with secukinumab and review of the literature. Issue 3 (29th April 2019) - Galluzzo, Marco; D'Adamio, Simone; Teoli, Miriam; Bianchi, Luca; Talamonti, Marina
Abstract: Acrodermatitis continua of Hallopeau (ACH) is a rare pustular psoriasis variant refractory to many conventional treatments. We report the successful treatment with secukinumab of a patient with a long history of ACH with marked onychodystrophy with frank pustulosis on the nail bed and with accompanying arthritis. Blockade of the IL‐17 receptor A has shown promise in the treatment of psoriatic erythroderma and generalized pustular psoriasis not responsive to conventional treatment. A rapid response was observed in our patient, in both skin lesions and arthritic symptoms, underlining the ability of secukinumab to improve symptoms beyond those of plaque psoriasis.